1983
DOI: 10.1136/bmj.286.6366.700
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Duchenne muscular dystrophy: experiences of parents of sufferers.

Abstract: Sixty nine parents of boys suffering from Duchenne muscular dystrophy were interviewed at home. The interview explored the parents' experiences at the time of their son's diagnosis. Many families had experienced distressing delays (average 2-5 years) between the time they first became aware of symptoms and the time of the diagnosis. On only 18 occasions were both parents told of the diagnosis together. One third of the parents were "not satisfied" with the way the diagnosis had been communicated. Parents want … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 6 publications
2
46
0
1
Order By: Relevance
“…15,17 Other studies have also shown that delays in DMD diagnoses are frustrating and stressful for parents particularly when they are given false reassurance and/or alternate/incorrect diagnoses. 9,23,24 Indeed, these experiences have been mirrored by parents of children with a range of other genetic conditions including fragile X syndrome (FXS), 25 Klinefelter syndrome 26 and childhood spinal muscular atrophy (SMA). 27 Diagnostic delay in DMD, and other genetic conditions, may occur for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…15,17 Other studies have also shown that delays in DMD diagnoses are frustrating and stressful for parents particularly when they are given false reassurance and/or alternate/incorrect diagnoses. 9,23,24 Indeed, these experiences have been mirrored by parents of children with a range of other genetic conditions including fragile X syndrome (FXS), 25 Klinefelter syndrome 26 and childhood spinal muscular atrophy (SMA). 27 Diagnostic delay in DMD, and other genetic conditions, may occur for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…At least 20% of cases of developmental delay have known genetic causes, for example, chromosomal abnormalities and single gene disorders, such as fragile X syndrome (FXS), Duchenne muscular dystrophy (DMD) and other dystrophies such as spinal muscular atrophy (SMA). In the case of FXS 2 and DMD, 3,4 there is evidence that parents may undergo a protracted journey before a diagnosis is made, with associated negative impacts on the families and lost opportunities for earlier intervention and reproductive decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Families living with DMD and those at risk for familial ALS found genetic information confusing and felt that they did not receive appropriate information or follow-up with healthcare professionals (Fanos et al, 2004;Firth, 1983;. Similarly, a group of 48 women at risk for being carriers of the DMD gene expressed uncertainty when trying to articulate and make sense of the statistical probability of their carrier status (Parsons & Clarke, 1993).…”
Section: Geneticsmentioning
confidence: 91%